2016
DOI: 10.1002/jor.23205
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of putative notochordal cell markers reveals CD24 and keratins 8, 18, and 19 as notochord‐specific markers during early human intervertebral disc development

Abstract: In humans, the nucleus pulposus (NP) is composed of large vacuolated notochordal cells in the fetus but, soon after birth, becomes populated by smaller, chondrocyte‐like cells. Although animal studies indicate that notochord‐derived cells persist in the adult NP, the ontogeny of the adult human NP cell population is still unclear. As such, identification of unique notochordal markers is required. This study was conducted to determine the spatiotemporal expression of putative human notochordal markers to aid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 49 publications
4
76
1
Order By: Relevance
“…qPCR analysis demonstrated significantly higher expression of a panel of previously‐identified NC markers (KRT8, KRT18, KRT19, CD24, and T) in porcine NC cells compared to AF cells (Figure B). This paralleled the expression patterns of these genes in the human system as previously described …”
Section: Resultssupporting
confidence: 79%
“…qPCR analysis demonstrated significantly higher expression of a panel of previously‐identified NC markers (KRT8, KRT18, KRT19, CD24, and T) in porcine NC cells compared to AF cells (Figure B). This paralleled the expression patterns of these genes in the human system as previously described …”
Section: Resultssupporting
confidence: 79%
“…Tie2 + preservation could, however, be augmented under hypoxic conditions, by supplementation of fibroblast growth factor 2 (FGF2) or synergistic FGF2 and hypoxic conditions (Figure C). Rodrigues‐Pinto et al demonstrated a lack of Tie2 expression during the development of the fetal notochord up to 18 weeks post‐conception, indicating that Tie2 might not play a role during development. Nonetheless, after fetal IVD explantation, isolation, and culture we were able to detect Tie2 + NPCs from both human and canine fetal tissue (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, functional analysis of the T transcription factor using U‐CH1‐N must be undertaken with caution. Furthermore, largely due to a paucity of data on IVD biology, we do not fully understand what criteria define “notochordal NP cell‐like cell line.” Although further studies are mandatory to address these issues, based on the observations of the past and present studies, we would like to propose the expression of notochordal NP cell‐specific markers, especially T and CD24, and the chondrogenic capacity as potentially the necessary conditions for “notochordal NP cell‐like cell line.” Nevertheless, bearing the limitations in mind, U‐CH1‐N is probably one of the best cell lines available to date to study the biology of notochordal NP cells.…”
Section: Discussionmentioning
confidence: 91%